"Notify Your Partners—It's the Law": HIV Providers and Mandatory Disclosure. (July 2014) - Lichtenstein, Bronwen; Whetten, Kathryn; Rubenstein, Casey
HIV care providers in the United States must counsel clients about disclosure to sexual partners and report anyone who is suspected of noncompliance. This study compared provider attitudes and practices in relation to counseling clients about mandatory disclosure in North Carolina and Alabama, the 2 states with similar HIV epidemiology but different laws for HIV control. Personal interviews were conducted with 20 providers in each state (n = 40). The results were analyzed in a qualitative, cross-comparison method to identify patterns of convergence or difference. Providers in both states believed that clients often failed to notify sexual partners and were secretive if questioned about disclosure. Differences in counseling styles and procedures for each state were noteworthy. Compared to Alabama, North Carolina had harsher penalties for nondisclosure, stricter and more standardized procedures for counseling, and providers expressed greater support for HIV criminalization. Although most North Carolina providers viewed the stricter standards as beneficial for HIV care and control, Alabama providers were likely to view such standards as a barrier to patient care. These results indicated a direct relation between state HIV law, provider attitudes, and counseling procedures for mandatory disclosure.